Relantionship Between Symbolic Self Awareness And Speaking Anxiety In College Students Of Biology Education Institute Of Islamic Religion Kerinci (FMIPA UNNES, 2022)
This study aims to determine the relationship between variables, namely the relationship between self awareness symbolic and anxiety speaking to college students of Biology Education Institute of Islamic Religion (IAIN) Kerinci. In this study are self awareness symbolic (X) and anxiety speaking (Y). This research is a quantitative study with a correlational approach. The population of this study was all 7 semester college students of Biology Education Institute of Islamic Religion (IAIN) Kerinci as many as 110 college students. The sample of this study was 90 college student who were determined through the Slovin formula technique with a significance level of 5%. The data in this study are data from the psychological scale of self awareness symbolic and the psychological scale of anxiety speaking is to use a Likert scale consisting of 25 statements for self awareness symbolic and 35 statements for anxiety speaking. The data analysis technique used is parametric statistics of Pearson Product Moment. The results of this study indicate that there is a relationship between self awareness symbolic and anxiety speaking. From the results of the comparison between sig and α values, obtained: Sig = 0,0000 < α = 0,05 so that the decision H1 is received, which is concluded that there is a relationship between self awareness symbolic and anxiety speaking. The relationship (correlation) between self awareness symbolic (X) and anxiety speaking (Y) very strong and positive, that is 0,870. Meaning that the higher the self awareness symbolic, the higher the anxiety of speaking. Vice versa, the lower the self awareness symbolic, the lower the anxiety of speaking.